Efektivitas Larvasida Alami Terhadap Nyamuk Culex Quinquefasciatus di Kota Pekalongan - Ayuningtiyas Tuti, Dita; Fitriyani, Lulu; Dara Juanita, Karoma; Salsabila, Intan; Adni, Lailatul; Aini Zahro, Reza; Fakarina, Fathimah; Irfiani, Widia; Fara Anindya, Labibah (JURNAL LITBANG KOTA PEKALONGAN, 2024)
Filariasis is an infectious disease caused by nematode infection that spreads through the Culex quinquefasciatus mosquito vector. Pekalongan City is one of nine filariasis endemic districts/cities in Central Java Province. Therefore, a control effort is needed that does not have a negative impact on the environment, namely through the use of vegetable larvicides. The purpose of this study was to determine the effectiveness of vegetable larvicidal extracts from lengkuas rhizome, lemon grass rhizome, betel leaf and zodia leaf. This research uses the True Experiment method. The samples in this study were Culex quinquefasciatus mosquito larvae taken randomly. Extract of lengkuas rhizome, lemongrass rhizome, and betel leaf were made in 1% and 5% variations with a volume of 200 ml. Meanwhile the zodia leaf extract was made with a 1% variation with a volume of 200 ml. The results showed that the higher the feed concentration, the higher the percentage of larvae mortality. This is in line with research conducted by Zunita (2018), that the more concentrated the concentration of a solution, the more poison that was ingested by the larvae so that the mortality of the larvae was higher.